Towards a better understanding of medical students’ mentorship needs: a self-determination theory perspective - Adam Neufeld (Canadian Medical Education Journal, 2021)
Introduction: Mentorship programs are ubiquitous in medical education. However, few emphasize equal development for learners and mentors, or incorporate clinical skills, which may be important for promoting medical students’ self-determination. Central to this consideration are the three basic psychological needs for autonomy, competence, and relatedness, described by Self-Determination Theory (SDT). Grounded in SDT, this study assesses the extent that meeting these needs, in a near-peer mentoring program, impacts learners’ and mentors’ motivation and perceived competence about learning and teaching of clinical knowledge, respectively.